The Efforts to Improve Teachers' Teaching Skills in Implementing Cooperative Learning Through Classroom Supervision: Upaya Meningkatkan Keterampilan Mengajar Guru Dalam Menerapkan Cooperative learning Melalui Supervisi Kelas - Syam Sahri (Journal of Vocational Education and Information Technology (JVEIT), 2021)
The background of this research is the lack of a class teacher teaching skills improvement program. Therefore, it is necessary to improve teacher teaching skills through classroom supervision at UPT SDN 20 Sitiung, Dharmasraya, West Sumatra Province in the 2020/2021 school year. The purpose of this study was to improve classroom teacher skills through cooperative learning. The method used is "School Action Research", which is divided into two cycles, and each cycle is divided into four stages, planning, action, observation and reflection. Data collection techniques are carried out by observing and evaluating directly the improvement of teacher skills in teaching. The data analysis technique used is quantitative and qualitative analysis. In the first round the proportion of teachers teaching through cooperative learning was 51.39%, still far from the minimum target of ≥70%, therefore it is necessary to carry out the second round. In the second cycle the teacher's teaching skills increased to 84.72% which had exceeded the goals to be achieved. The conclusion that can be drawn is the effort to increase the application of cooperative learning teaching skills of teachers in this learning process can be applied in UPT SDN 20 Sitiung.